CONTAMINATION OF COMMERCIAL POULTRY FEEDS AND FEED INGREDIENTS WITH ASPERGILLUS FLAVUS AND AFLATOXIN B1 IN PUNJAB PAKISTAN - A. Rafique; M. T. Javed; S. Shahid Ali (Journal of Animal and Plant Sciences, 2018)
The occurrence of mycotoxins in feed is a major problem in poultry because it deteriorates the feed quality and thus contributes to economic losses in the form of decreased profitability. The study was carried out to assess the prevalence of A. flavus and AFB1 in poultry feed and feed ingredients during one full year. Results revealed that 34.2% feed samples were contaminated with A. flavus and 29.2% with AFB1, while 26.9% and 26.4% samples of feed ingredients were found contaminated with A. flavus and AFB1, respectively. The contamination with A. flavus and AFB1 was highest for corn followed by cotton seed meal and broken rice. Higher percentages of samples were found contaminated during humid summer or in spring. The AFB1 contamination in feed ingredients revealed a significant difference. More than 30% samples of corn, broken rice and cotton seed meals were found contaminated with AFB1 and more than 50% of corn and 40% of broken rice and cotton seed meal with A. flavus. The highest percentages of feed samples were found contaminated with A. flavus and AFB1 during July to September. Majority of feed samples had AFB1 levels were below 200ppb. The feed and feed ingredients were invariably contaminated with A. flavus and AFB1 and the prevalence varied with the season and there is a direct correlation between A. flavus and AFB1 contamination. known as mycotoxins are structurally diverse and
Keywords: A. flavus; AFB1; feed; feed ingredients; Pakistan.